Parent and Teacher Training Increases Medication Adherence for Primary School Children With Attention-Deficit/Hyperactivity Disorder - Zheng, Xiaofei; Shen, Li; Jiang, Lian; Shen, Xiao; Xu, Ying; Yu, Guangjun; Wang, Yu (Frontiers in Pediatrics, 2020)
Objective: Attention-Deficit / Hyperactivity Disorder (ADHD) is a common neurobiological disorder for which effective and safe medication is recommended as first line treatment. However, many parents and teachers do not believe that ADHD is a disorder or do not accept medication treatment in China. Our study aimed to investigate the clinical effect of employing four- week, session-based training for both parents and teachers in improving medication adherence for primary school children with ADHD. Methods: From January 2018 to December 2018, a total of 5118 primary school children were screened. Amongst 211 children diagnosed with ADHD, 116 were assigned to the intervention group and 95 to the control group. This study provided systematic training for parents and teachers in the intervention group. The training consisted of education about the disorder and ADHD behavioral intervention for both parents and teachers as well as classroom management techniques for just the teachers. A cluster randomized controlled trial (RCT) was conducted to investigate the effect of this training at 6 months follow-up. Results: After training, more parents and teachers believed that ADHD is a neurobiological disorder and that medication is the first line treatment. At 6 months follow-up, the Medication Adherence Report Scale (MARS) score for the intervention group was 22.8±0.75 and 16.5±1.63 for the control group (t=5.217, P<0.01). Based on parents’ reports and medical records, 82 children (70.69%) were continuously taking medication for 6 months in the intervention group, while only 35 children (36.84%) were doing so in the control group. In the intervention group, the mean SNAP-IV score was 1.98±0.42 at baseline but 0.99± 0.31 at 6 months follow-up. In the control group, the mean SNAP-IV score was 1.89±0.47 at baseline but 1.37±0.42 at 6 months follow-up (F=2.67, P=0.009). Factors influencing medication adherence for children with ADHD were parent beliefs, teacher beliefs, socioeconomic status, adverse effect, insurance coverage, gender and trust of the medical system. Conclusions: Our findings indicate that comprehensive training programs improve the understanding of ADHD and medication adherence for both children’s parents and teachers, providing a promising approach for improving clinical efficacy for children with ADHD.